An Examination of College Counselors' Work With Student Sex Addiction: Training, Screening, and Referrals. Issue 1 (6th April 2018) - Giordano, Amanda L.; Cashwell, Craig S.
Abstract : Given the prevalence of sex addiction (SA) among collegiate populations, the authors designed this study to examine college counselors' training in SA, use of formal assessments, and referrals to support groups. Results indicated that 84.4% of college counselors ( N = 77) had at least one client present with SA‐related issues in the past year. Findings suggest the need for improvement in counselor training in SA, use of formal assessments, and referral practices.